Study on the etiology of fibropapillomatosis of olive ridley sea turtles (Lepidochelys olivacea) nesting in the National Wildlife Refuge at Ostional, Guanacaste, Costa Rica - Brenes-Chaves, Laura (2013)
Sea turtle fibropapillomatosis is an emerging disease characterized by a proliferation of cutaneous papillomas, fibromas, and fibropapillomas and occasional visceral fibromas. This paper aims to contribute to the etiology of fibropapillomatosis in olive ridley sea turtles (Lepidochelys olivacea) nesting in Ostional National Wildlife Refuge. Twenty-six olive ridley turtles with cutaneous fibropapilloma were sampled and 24 healthy olive ridley turtles served as controls. Biopsies were taken of the cutaneous tumors in sick sea turtles, as well as skin biopsies from control subjects, and blood samples were collected from all turtles. Tumorous samples and skin samples were microscopically analyzed in order to differentiate the histological factors resulting from the disease pathogenesis, where the main histological findings were papillary epidermal hyperplasia, orthokeratotic hyperkeratosis, spirorchid-like eggs in the dermis, and eosinophilic cytoplasmic inclusion. Hematology and blood chemistry studies were conducted on blood samples, and MCHC, heterophils, lymphocytes, monocytes, AST, total protein, albumin and globulin values were significantly different between healthy turtles and turtles with tumors. A PCR test was also conducted in the samples to determine the presence of herpesvirus and papillomavirus as possible etiologic agents, where the papilomavirus was absent in all the samples, while the herpesvirus was present in 69.23% of the tumors, this being the most probable etiological agent of fibropapillomatosis.